Simulasi Penggunaan Frekuensi Milimeter Wave Untuk Akses Komunikasi Jaringan 5G Indoor - Toha Ardi Nugraha; Alfin Hikmaturokhman (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2017)
Millimeter Wave (mmWave) is a solution to overcome of frequency limitations in 5G technology implementations using high frequency domain. This research discusses about mmWave frequency selection for 5G technology using empirical models in indoor propagation model. Several MmWave frequencies are simulated on indoor office environment. Based on simulation with InH placed in each room 5x5 meter size, it will be more effective using 60GHz, compared to 38Ghz, 28GHz, and 5GHz and also unlicenced 2.4. The average SIR will better at mmWave frequencies in the 60GHz with 33.97 dB and the average received signal is -73.87 dBm. Overall, it can also be concluded that the InH device with low frequency is not suitable applied indoors with massive deployement, it can be interference, for exampe using unlicenced 2.4GHz and 5GHz, receiver only gets average SIR of approximately 5dB. Keywords-5G, Indoor, Milimeter Wave, Indoor Hotspot